Diversidade e estrutura genética de Pterodon emarginatus vogel (leguminosae) no cerrado - Sousa, Daniel Ferreira de (2020)
Pterodon emarginatus Vogel, popularly known as white sucupira, has characteristics that allow its exploitation as a timber, ornamental and medicinal resource. Knowing the genetic variability in natural populations of a plant genetic resource is important for defining strategies for its use and conservation. The present study had as objective to know the genetic diversity of natural populations of P. emarginatus in the Brazilian cerrado, for use and conservation purposes. 302 individuals were collected, from 13 Brazilian cerrado populations. These individuals were analyzed using 10 microsatellite markers. The detection of the genotypes was performed using the ABI-3500 genetic analyzer (Applied Biosystems). The quality of the loci was evaluated based on estimates of probability of identity and probability of exclusion of paternity, in the Identity4 program. The analyzes of diversity and genetic population structure were performed in the GDA programs and by the hierfstat package, in environment R. The cluster analysis was performed by the Bayesian method, using the STRUCUTRE program. The genetic divergence (pairwise FST) and the Mantel test were estimated, using the hierfstat and Vegan packages in environment R. The presence of genetic discontinuity was verified with the application of the Monmonier algorithm. The identification of priority populations for conservation was performed by the Greedy algorithm, in an R environment. The battery of loci proved to be adequate for the analysis of individual discrimination and for population genetic studies, since the probability of identity was low (PI = 2, 4109 x 10-11) and the exclusion of paternity was high (Q = 0.9999). An average of 15.9 alleles were identified per locus. The observed heterozygosity (0.521) was less than the expected heterozygosity (0.654). The populations exhibited a significant population genetic structure (θp = 0.104), with the presence of inbreeding due to the reproductive system (f = 0.207). The inbreeding of the population group was also high and significant (F = 0.290). Six groups were detected by Bayesian analysis. No relationship was detected between genetic and geographical distance. The populations of Araguaçu TO and Porangatu GO showed genetic discontinuity with four other populations. It was not possible to establish a minimum number of priority populations for conservation, as there is a need to conserve all of them (13) in order to sample all the alleles identified in the present study. This study reveals that the natural populations of P. emarginatus have high genetic diversity, but this diversity .is structured among populations and that there is inbreeding within populations due to the reproductive system. In addition, the genetic divergence is not explained by the geographical distance and the populations have a low redundancy of allelic richness. Such results imply the need for a greater sampling effort, both of individuals and populations, in works aimed at the conservation and use of the species.